HUBUNGAN ANTARA PEMBERIAN ASI EKSKLUSIF DENGAN PERKEMBANGAN BAYI USIA 7 SAMPAI 12 BULAN DI DESA TIPAR KIDUL WILAYAH KERJA PUSKESMAS AJIBARANG I - Martyarini Budi Setyawati; Etika Dewi Cahyaningrum (Viva Medika, 2013)
Exclusive breastfeeding or breast-feeding exclusively is babies given only breast milk alone without the addition of liquid and solid foods until the age of 6months. Breastfeeding has enormous benefits for the baby's development.Exclusive breast milk contains many substances that are needed especially for thebaby's body immunity so that the child is not easily affected by the disease. Thisstudy aims to determine the relationship between exclusive breastfeeding with thedevelopment of infants aged 7 to 12 Months in Tipar Kidul village PuskesmasAjibarang I. This research method is a correlation analytic research with crosssectional approach. Sampling techniques in this study using purposive sampling.This research sample is all mothers with infants aged 7 to 12 months in TiparKidul village Puskesmas Ajibarang I as many as 40 respondents. Measuringinstruments used are KPSP and type of data is primary data. Results of this research was the respondents did not provide exclusivebreastfeeding by 23 respondents (57.5%). Most of the baby's development isappropriate as much as 18 respondents (45%). There is a relationship betweenexclusive breastfeeding with the development of infants aged 7 to 12 months witha value of Ï-value <Î± (0.000 <0.05), then Ho is rejected and Ha accepted. Key words: Exclusive Breastfeeding, Baby's Development